Islamic Radical Movement, Jihad, and Terorism in Indonesia - Fahmi Irfani (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses the recent development of Islamic world which related to radical movements Southeast Asia and the problem with the nation of jihad or religious terrorism. The radical movements in the history of Islamic development began in the early phase, it was marked by the presence of Khawarij group during the era of sahabat. This Khawarij group appeared due to the dissatisfaction of the political decision between Ali ad Muawiyah, thus caused the appearance of radical understanding by infidled (mengkafirkan) groups outside their group. The subsequent development of Islamic radicalism in the global world continuous to appear in different forms, and it also appears in every country including Indonesia. The incident of Black September, ISIS, Al-Qaeda, Jamaah Islamiyah, are the new forms of salafi jihad that uses terrorism to achieve their goal, and it caused the controversy in the Islamic world, is that considered as jihad or terrorism?